2012
DOI: 10.1167/iovs.12-10593
|View full text |Cite
|
Sign up to set email alerts
|

Capsaicin-Induced Corneal Sensory Denervation and Healing Impairment Are Reversed by NGF Treatment

Abstract: PURPOSE. We aimed to evaluate the nerve growth factor (NGF) pathway and its influence on corneal healing mechanisms in normal conditions and in an animal model of corneal denervation induced by capsaicin.METHODS. Peripheral sensory damage was induced in rat pups by subcutaneous injection of capsaicin and the effects evaluated by hot-plate test, corneal nerve count, and tear secretion. Corneal damage was induced in capsaicin-treated and -untreated rats by epithelial scraping. Healing rate; NGF pathway (NGF, tyr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
33
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 34 publications
4
33
0
Order By: Relevance
“…As a consequence, the efficacy of topical treatment with murine NGF (mNGF) eye drops was evaluated both in animal models and in patients affected by neurotrophic and autoimmune corneal ulcers [1215]. In all these cases, therapeutic efficacy was associated with a good safety profile [1315].…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, the efficacy of topical treatment with murine NGF (mNGF) eye drops was evaluated both in animal models and in patients affected by neurotrophic and autoimmune corneal ulcers [1215]. In all these cases, therapeutic efficacy was associated with a good safety profile [1315].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have described conflicting results related to the effects of manipulating the NGF pathway. Administration of NGF to the cornea has been shown to increase presence of corneal nerves and increase rates of epithelial proliferation [30], [32], [33], improve corneal healing after capsaicin administration and epithelial scraping [34], and increase wound closure [28]. Other studies have shown that NGF has no effect on wound closure [27].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the levels of NGF are increased in the cornea after injury. This NGF increase is impaired in denervated cornea, which shows a delayed healing [49]. NGF treatment of denervated cornea improved corneal healing and increased the expression levels of the corneal stem cell marker p63 [50].…”
Section: Innervation and Corneamentioning
confidence: 94%